Tin slag polymer concrete strengthening by basalt and aramid fiber reinforced polymer confinement - Muhamad Soffi, Manda; Mohd Ruzaimi, Mat Rejab; Shukur, Abu Hassan; Mat Uzir, Wahit; Selvi Binoj, Joseph; Brailson Mansingh, Bright; Siti Safarah, Amirnuddin; Ali, Alamry; Lim Goh, Kheng; Nurhadiyanto, Didik (Prints Publications Private Limited, 2022)
This study investigates the potential of Tin Slag Polymer Concrete (TSPC) strengthening through confinement using basalt fiber reinforced polymer (BFRP) and aramid fiber reinforced polymer (AFRP) confinement. TSPC short cylindrical column samples have been wrapped with BFRP and AFRP in a single layer (30 mm overlap) using Sikadur-330 epoxy and final samples were coded as TSPC-UC, TSPC-BF and TSPC-AF for unconfined, BFRP and AFRP for confined respectively. After curing for 30 days at room temperature, compressive test has been performed to know the strength, modulus, strain, fracture energy and failure modes of unconfined and confined TSPC. Test result shows that AFRP confinement (114.24 MPa) provide more upsurge in strength enhancement compared to BFRP (81.52 MPa). Fracture energy value of TSPC-AF (821.18 J) is higher than TSPC-BF (538.66 J), but compressive modulus of TSPC-AF (3.23 GPa) is lower than TSPC-BF (4.32 GPa). In addition, yield stress value of TSPC-AF (80.71 MPa) is higher than TSPC-BF (57.21 MPa). Moreover, stress-strain curve and failure mode has shown that TSPC-AF exhibit higher degree of brittleness compared to TSPC-BF. Finally, it is noticed that there are some similarities in strength augmentation of TSPC amid BFRP and glass fiber reinforced polymer (GFRP) as well as between AFRP and carbon fiber reinforced polymer (CFRP) confinement.